Competitive oxidation and ubiquitylation on the evolutionarily conserved cysteine confer tissue-specific stabilization of Insig-2 - Zhang-Sen Zhou (Nature Portfolio, 2020)
The protein Insig-2 negatively regulates lipid biosynthesis and is short-lived in liver cells but stable in muscle cells. Here, the authors show that in muscle cells producing reactive oxygen species, there is increased oxidation compared to ubiquitination of Insig-2, stabilising Insig-2 and reducing lipid biosynthesis.